Association of plasma aldosterone concentration with peripheral artery disease in hypertensive patients: insights from a large cross-sectional analysis - Zhang, Yingying; Cai, Xintian; Song, Shuaiwei; Hu, Junli; Zhou, Pan; Cai, Kangxin; Ma, Rui; Ma, Huimin; Shen, Di; Yang, Wenbo; Zhang, Delian; Luo, Qin; et al. (Frontiers in Cardiovascular Medicine, 2025)
ObjectivesTo investigate the relationship between plasma aldosterone concentration (PAC) and the prevalence of peripheral artery disease (PAD) in hypertensive patients and to determine any potential threshold effects.MethodsThis cross-sectional study analyzed data from 13,157 hypertensive individuals from the People's Hospital of Xinjiang Uygur Autonomous Region, China. PAD was diagnosed based on an ankle-brachial index (ABI) of ≤0.90. A multivariate logistic regression model was utilized to evaluate the association between PAC and PAD, and a generalized additive model (GAM) was employed to explore non-linear relationships.ResultsThe fully adjusted logistic regression model revealed a significant positive association between PAC and PAD, with an odds ratio (OR) [95% confidence interval (CI)] of 1.06 (1.04, 1.08) per unit increase in PAC. The GAM identified a critical threshold at 17.00 ng/dl for PAC, above which the prevalence of PAD increased by 9% for each unit increase in PAC, with an OR (95% CI) of 1.09 (1.06, 1.11). Sensitivity and subgroup analyses confirmed the robustness of these findings.ConclusionThis study establishes a non-linear relationship between PAC and the prevalence of PAD in hypertensive patients, with a critical threshold at 17.00 ng/dl. These findings underscore the importance of aldosterone homeostasis in vascular health and the need for further large-scale, prospective studies to validate these results and explore their clinical implications.